Prevalence of nephropathy in type 1 diabetes in the Arab world: A systematic review and meta‐analysis. Issue 7 (8th June 2018) - Abdel‐Motal, Ussama M.; G, Akila; Abdelalim, Essam M.; Ponnuraja, Chinnaiyan; Iken, Khadija; Jahromi, Mohamed; Doss, George Priya; El Bekay, Rajaa; Zayed, Hatem
Summary: The aim of this study was to conduct a systematic review and meta‐analysis and determine the prevalence of diabetic nephropathy (DN) among Arab patients with T1D. A systematic literature search was conducted using 4 different literature databases (PubMed, ScienceDirect, Web of Science, and Embase) to capture all relevant data about Arab patients with T1D that had DN. Meta‐analysis and systematic review were performed using the random effect model, and the heterogeneity of the studies was assessed using the Q‐test, I2, and Tau‐squared statistics. Publication bias was assessed using the funnel‐plot test. Our search strategy captured 372 studies in only 10 out of the 22 Arab countries in a period of 48 years (1969‐2017); of which, 41 met our inclusion criteria for full article analysis, of those, 15 were eligible for meta‐analysis. We estimated the prevalence of DN among Arab people with T1D to be 18.2% (95% confidence interval 13.1%‐24.8%). In conclusion, DN prevalence is underexplored among Arab patients with T1D and represents a significant risk for the well‐being of Arab patients with T1D. Therefore, there is an urgent need for comprehensive epidemiological studies for DN among Arab patients with T1D.